Online peer-led group reflective practice in higher education: a seminar-based project evaluation. Issue 6 (2nd November 2022) - Palacios, Nahielly; Rafique, Rumana; Kwihangana, Felix; Zhao, Xian
ABSTRACT: This study explores the effects of online Peer-Led Group Reflective Practice (PLGRP) on students undertaking their master's degree in the UK, during the Covid-19 pandemic. First, it provides an overview of the online seminar-based project called Holistic Academic and Research Reflective Practice (HARRP) which fostered the PLGRP pedagogical approach presented and evaluated here. Next, it delves into the reflective pedagogical approaches that informed the project design, before looking at its effects on students. A qualitative methodology enabled the implementation of an open-ended questionnaire which helped capture students' thoughts on the project. Results of a thematic analysis suggest that online PLGRP provided opportunities for students to develop their academic and researcher reflexivity, researcher competence as well as their independent and interdependent learning skills. Issues around lack of time to attend seminars and lack of familiarity with working in peer-led reflective groups enabled further suggestions and improvements to the HARRP project. The contribution of this study lies in the way in which PLGRP approach is designed and operationalised with the purposes of helping students make sense of their academic and research journey individually and in groups. This study also shows how individual and peer-led group reflective practices shape one another.